Empowering Farmers to Combat Mixed Gastro-Intestinal Parasitism in Small Ruminants: A Pathway to Boosting India’s Economy - Charitha Vutharamalluru, Gnani; Gaddam, Tejeswar; Kumar Nagaram, Vinod; Babu Potu, Ramesh; Devarakonda, Srikala; Jarasangi, Bhagyalakshmi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Parasitic infections often cause production loss and are a major constraint for the livestock sector. The aim of the current study was to take up a detailed investigation of the flock comprising of 850 sheep (600 adults and 250 lambs) and the surrounding areas. Farm visit and clinical examination revealed some of the animals quite sick, recumbent, dull, depressed and diarrhoeic with jowl edema. The majority of the animals showed malnutrition, poor grazing quality, and low weight again. Faecal samples (n=250) examination revealed the presence of Coccidia (Eimeria intricate; E. pallida) (24.1%), Monieza spp. (21.1%) and its segments along with Strongyle and Trichuris eggs. Haemato-biochemical examination revealed severe anaemia, haemolysis of RBC, neutrophilia, eosinophilia, leucocytosis, deficiency of total protein, albumin, and increased levels of ALT in the serum. It was concluded that lack of good management practices, poor nutrition and contaminated water source (fish ponds) deteriorated the health condition of the animals. The farmers were suggested for the inclusion of concentrate mixture, haematinics to the feed along with routine deworming (Albendazole @ 100 mg/kg b.wt. and Ivermectin @ 0.02 mg/kg b.wt.) to relieve the worm burden. The farmers were enlightened on complete management practices and periodical vaccinations dosing and advised on the protocols for the prevention and control of diseases.